PENGARUH STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING: Studi pada perusahaan Properti, Real Estate Dan Konstruksi Periode 2015-2017 - Mayang Rizka Maulida, - (2019)
This research is using quantitative study aimed to see whether there are influence of capital structure variable on firm value with profitability as intervening variable of the Property, Real Estate and Construction companies listed on the Stock Exchange during 2015-2017. This study uses 41 sample companies selected by purposive sampling method. Testing the hypothesis in this study was used Data Panel Regression and Path Analysis Techniques with Eviews program and a significance level of 5% (0.05). The results of these tests indicate that (1) there is a positive and significant influence of capital structure variables on profitability, (2) there is a positive and significant influence of capital structure variables on firm value, (3) there is a positive and significant influence of profitability variables on firm value, (4) there is no significant influence of capital structure variables on firm value through profitability.